Bilateral Ganglionic Haemorrhagic Stroke Complicating Suspected Meningococcaemia: A Case Report (2020)
Haemorrhagic stroke in pyogenic meningitis is a rare complication, accounting for about 2% of all complications. It often results from disseminated intravascular coagulation, a complication of bacterial meningitis, and portends a poor prognosis. A superimposed intracranial haemorrhage, although extremely rare, is associated with a high mortality rate. We report a child who had haemorrhagic stroke during the acute phase of bacterial meningitis. The diagnosis was made during post-mortem examination. It was discovered that she had suffered haemorrhagic necrosis of both basal ganglion nuclei. Early imaging is advised in meningitis patients presenting with altered levels of consciousness to detect cerebrovascular complications. Introduction Meningitis is a severe infection of the leptomeninges caused by viruses, bacteria, parasites, or fungi. Mortality rates are as low as 2% in infants and children and as high as 20–30% in neonates and adults. Cerebral vasculopathy is a complication of bacterial meningitis, with ischaemic stroke being much more common than haemorrhagic stroke, usually occurring during the acute phase of meningitis. Bacterial meningitis remains a leading cause of mortality from infectious disease globally, and the neurologic complications associated with this disease are a major contributor to mortality. In the paediatric age group, meningitis usually develops after encapsulated bacteria colonising the nasopharynx are disseminated into the blood and breach the blood–brain barrier, colonising the leptomeninges where they rapidly multiply. The body’s immune system mounts a response against the microbes. Studies in rabbits with C3 deficiency have demonstrated the importance of the complement system in meningitis. Genetic deficiencies in early response cytokines such as TNF-α, IL-1β, and IL-6 predispose individuals to central nervous system infections that may run a fulminant course. Cerebral vasculopathy in bacterial meningitis can occur from infection by organisms such as Streptococcus pneumoniae, Neisseria meningitidis, Haemophilus influenzae, and Staphylococcus aureus. Haemorrhagic stroke from bacterial meningitis is rare. Various pathophysiological mechanisms have been proposed, including focal hyperperfusion from loss of cerebral autoregulation, disseminated intravascular coagulation (DIC), localized vasculitis, and microaneurysm formation. This complication confers a worse prognosis on meningitis, with higher morbidity and mortality. Early diagnosis of cerebrovascular events complicating meningitis allows for prompt surgical intervention to improve prognosis. We report the case of a nine-year-old female child who presented and died within 24 hours of presentation from bilateral basal ganglia haemorrhages due to acute bacterial meningitis. Case Report A nine-year-old female was seen in the paediatric clinic with a history of fever, sore throat, non-productive cough, vomiting, and generalized body weakness. She was a known asthmatic. She was nebulized and placed on antibiotics and antimalarials. Her condition deteriorated later in the night. She was brought into the children’s emergency unit with a six-hour history of fever and lack of response to calls for two hours. She was admitted into the intensive care unit and managed as a case of meningitis. On presentation, she was acutely ill, anicteric, and not cyanosed. There was tachycardia, with a blood pressure of 90/60 mmHg. She was tachypnoeic and dyspnoeic, with crepitations in the lower lung zones. The Glasgow Coma Score (GCS) was 13, the neck was supple, and Kernig’s and Brudzinski’s signs were negative. Pupils were 3 mm bilaterally and reacted briskly to light. Muscle tone and reflexes were normal, with no facioparesis. Laboratory tests revealed thrombocytopenia (platelet count 85,000/mm³), elevated INR (3.5), and deranged prothrombin time (41 seconds). Blood culture did not yield growth. Her GCS dropped to 6 within two hours of admission; she had two episodes of tonic convulsions and went into refractory shock despite intravenous boluses and adequate inotropic support. Nasogastric aspirate was bloody, and blood stains were seen in her perineum. She desaturated with SpO₂ of 65% while on 100% oxygen. Her GCS further dropped to 3 within fourteen hours of admission. She was managed with intravenous antibiotics, fluids, steroids, and antimalarials. Cranial imaging was not performed prior to death. She spent a total of seventeen hours on admission before demise. Although there was no growth on blood culture and a lumbar puncture was deferred, she was managed as a possible case of meningococcaemia. At autopsy, there was linear ecchymosis on the arm and ecchymosis on the right ventricular wall. Mesenteric and splenic haematoma with haemorrhagic gastropathy were noted. The lungs were markedly congested, showing features of diffuse alveolar damage with microthrombi. Histology of the kidneys showed extensive tubular necrosis, and both adrenal glands showed haemorrhagic infarctions. The brain was heavy, weighing 1600 g (normal 1150–1250 g), with greyish-white exudates over the convexities of the parietal lobes and superior cerebellar hemispheres; there was no frank pus. Coronal sections of the cerebral hemispheres showed bilateral basal ganglia haemorrhages affecting both lenticular nuclei and sparing the caudate. Histology revealed haemorrhagic infarction of the basal ganglia with associated microthrombi. The patient had no features of hypertension, and the vessels showed only mild fatty streaks of the abdominal aorta.